Injury and performance related biomechanical differences between recreational and collegiate runners - Evans, Ryan J.; Moffit, Tyler J.; Mitchell, Peter K.; Pamukoff, Derek N. (Frontiers in Sports and Active Living, 2023)
Introduction Running related injuries (RRI) are common, but factors contributing to running performance and RRIs are not commonly compared between different types of runners. Methods We compared running biomechanics previously linked to RRIs and performance between 27 recreational and 35 collegiate runners. Participants completed 5 overground running trials with their dominant limb striking a force plate, while outfitted with standardised footwear and 3-dimensional motion capture markers. Results Post hoc comparisons revealed recreational runners had a larger vertical loading rate (194.5 vs. 111.5 BW/s, p < 0.001) and shank angle (6.80 vs. 2.09, p < 0.001) compared with the collegiate runners who demonstrated greater vertical impulse (0.349 vs. 0.233 BWs, p < 0.001), negative impulse (−0.022 vs. −0.013 BWs, p < 0.001), positive impulse (0.024 vs. 0.014 BWs, p < 0.001), and propulsive force (0.390 vs. 0.333 BW, p = 0.002). Adjusted for speed, collegiate runners demonstrated greater total support moment (TSM), plantar flexor moment, knee extensor moment, hip extensor moment, and had greater proportional plantar flexor moment contribution and less knee extensor moment contribution to the TSM compared with recreational runners. Unadjusted for speed, collegiate runners compared with recreational had greater TSM and plantar flexor moment but similar joint contributions to the TSM. Discussion Greater ankle joint contribution may be more efficient and allow for greater capacity to increase speed. Improving plantarflexor function during running provides a strategy to improve running speed among recreational runners. Moreover, differences in joint kinetics and ground reaction force characteristics suggests that recreational and collegiate runners may experience different types of RRI.